2021
DOI: 10.1016/j.econlet.2021.109730
|View full text |Cite
|
Sign up to set email alerts
|

Can news help measure economic sentiment? An application in COVID-19 times

Abstract: for their comments and suggestions. We also thank all participants at the internal seminar of the Banco de España for their comments. The views expressed in this paper are our own and do not necessarily reflect the views of the Banco de España or the European System of Central Banks (ESCB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…As an empirical exercise, we construct a text-based indicator that helps track economic activity, as described in [1]. It is based on a similar procedure that is used to elaborate the economic policy uncertainty indicator, i.e., it relies on counting the number of articles in the Spanish press that contain specific keywords.…”
Section: A Supervised Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As an empirical exercise, we construct a text-based indicator that helps track economic activity, as described in [1]. It is based on a similar procedure that is used to elaborate the economic policy uncertainty indicator, i.e., it relies on counting the number of articles in the Spanish press that contain specific keywords.…”
Section: A Supervised Methodsmentioning
confidence: 99%
“…Central banks make intensive use of structured databases to carry out their functions, whether in the banking supervision, financial stability, or monetary policy domains, to mention the core ones. 1 Some examples of individual data are firms' balance sheets (see, e.g., [51] or [6]), information relating to the volume of credit granted by financial institutions to individuals and firms, or the data relating to agents' financial decisions (see, e.g., [5]). In the area of macroeconomics, the main source of information tends to be the national accounts or the respective central bank sources, although a great deal of other information on the economic and financial situation is also published by other bodies: e.g., social security data, payroll employment data (Bureau of Labor Statistics), stock prices (Bloomberg), and house prices (real estate advertising web platforms).…”
Section: New Data Sources For Central Banksmentioning
confidence: 99%
See 2 more Smart Citations
“…Investor sentiment was studied also in connection with mass-media influences (Sun et al 2021). Aguilar et al (2021) proposed a novel newspaper-based sentiment indicator in order to monitor real-time changes within the Spanish economy. The results showed that the efficiency of the new indicator in forecasting GDP evolution was superior to that of the economic sentiment indicator measured by the European Commission.…”
Section: Literature Reviewmentioning
confidence: 99%